Saints and Non-Saints. Patronage in Hanging Cultural and Political Conditions - Bartnicki Adam R. (Studies in Logic, Grammar and Rhetoric, 2025)
Patrons have played a very important role in the past not only in re-ligious terms, but also as a keystone connecting local communities and even dif-ferent countries. They therefore influenced international relations. Today, they still play a role at the local and regional government or school levels. They are an element that integrates local communities. This analysis is an attempt to define the phenomenon of patronage and to analyze the cultural and political dimension of the phenomenon, showing how religious, political, and ideological issues have affected the perception and the cultural and political role of patron-age in history. Each historical period gave the function of “patronage” its own peculiar feature and the purpose of this paper is to show the phenomenon of the formation of historical memory through the veneration of “saint and non-saint” patrons and to grasp the causes and nature of changes in the perception of patronage.